Snow avalanche activity in Żleb Żandarmerii in a time of climate change (Tatra Mts., Poland) - Gadek, Bogdan (2017)
This paper reports from a survey of the occurrence of large avalanches in Żleb Żandarmerii. This couloir is known to be one of the most hazardous avalanche paths in the Tatra Mountains and has one of the longest histories of avalanche observation. This survey looked at the runout distance, return period, dynamics and geoecological implications of avalanches in the context of current climate change. The study took advantage of the longest record of meteorological data available in the Tatra Mountains, as well as archival avalanche observations, topographical maps, orthophotomaps and a high-resolution digital terrain model. Avalanche data were obtained using geomorphological and dendrogeomorphic methods and through modelling with the RAMMS numerical avalanche dynamics simulation software. The largest avalanches reach the foot of its counter slope. Their length, release volume, flow velocity and pressure can exceed respectively 1000 m, 80 000 m3, 45 m/s and 600 kPa. The results of our study suggest that current climate warming has been accompanied by thinning and shortening of the duration of snow cover, as well as by an upward expansion of the timberline (including in the large-avalanche runout zones) of up to 80 m since the mid-1920s. No distinct temporal trend was identified in the large avalanche return period since 1909, but their mass and intensity have declined. Forests and timberline expansion were found to have no influence on the extent of the avalanches in our study, while ground relief could determine both their downward extent and lateral expansion.